2010
DOI: 10.1146/annurev-genet-102108-134841
|View full text |Cite
|
Sign up to set email alerts
|

Telomeric Strategies: Means to an End

Abstract: What really defines a telomere? Telomere literally is an amalgamation of the Greek words "telos," meaning end, and "mer," meaning part. In practice, it refers to the extremities of linear chromosomes. The defining functions of chromosome extremities can be summarized in two main categories. First, chromosome ends trick the cell into not identifying them as damage-induced double-strand DNA breaks (DSBs). An internal DSB immediately triggers cell-cycle arrest and is repaired to ensure that genome integrity remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
177
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(177 citation statements)
references
References 221 publications
(201 reference statements)
0
177
0
Order By: Relevance
“…In QTIP, the proteins in the different cell populations to be compared are differentially labelled by incubating the cells in medium containing either heavy isotopes ([ 13 C 6 15 N 4 ]Arg (R10) and [ 13 C 6 15 N 2 ]Lys (K8)) or light isotopes (Arg (R0) and Lys (K0)) (Approach A, Fig. 1a).…”
Section: Implementation Of Qtipmentioning
confidence: 99%
See 1 more Smart Citation
“…In QTIP, the proteins in the different cell populations to be compared are differentially labelled by incubating the cells in medium containing either heavy isotopes ([ 13 C 6 15 N 4 ]Arg (R10) and [ 13 C 6 15 N 2 ]Lys (K8)) or light isotopes (Arg (R0) and Lys (K0)) (Approach A, Fig. 1a).…”
Section: Implementation Of Qtipmentioning
confidence: 99%
“…Telomeric DNA consists of simple repetitive DNA sequences (5 0 -TTAGGG-3 0 /5 0 -CCCTAA-3 0 repeats in humans) of several kilobases and terminates with single-stranded (ss) 3 0 overhangs measuring a few hundred nucleotides 6 . Telomeric DNA is assembled with specialized telomere-binding proteins.…”
mentioning
confidence: 99%
“…In contrast, addition of Zscan4 resulted in 8.36-fold, 6.20-fold and 4.37-fold increases in T-SCE frequency in OSKMZ-infected MEFs on days 3, 6 and 9 post-infection ( Figure 4C and 4D), respectively. We also analyzed expression levels of shelterin components and found that Trf2, Pot1b and Rap1, which can inhibit T-SCE after replication [39,40], were repressed when Zscan4 was overexpressed ( Figure 5A). Other shelterin proteins, Trf1, Pot1a, Tpp1 and Tin2, were not repressed ( Figure 5B).…”
Section: Zscan4 Promotes Telomere Elongation During Reprogrammingmentioning
confidence: 99%
“…Although it is essential to sequester the DNA end from nuclease and DNA repair activities for much of the cell cycle, during S phase the telomere must be made accessible to telomerase and the DNA replication machinery 1 .…”
mentioning
confidence: 99%